La interculturalidad en la Educación Inicial. - Gallo Villacis, Blanca Lucia (2018)
The research project on interculturality in early childhood education has been developed with the purpose of studying in depth the factors that intervene in the relationships of respect and tolerance towards cultural diversity on the part of the educational community, as part of the processes comprehensive training of students. The research problem has been considered based on the deficient educational strategies to promote an intercultural education, in which the different cultural expressions that are part of the personality and history of each student are included and valued. The process of construction of intercultural education needs to be strengthened from the educational authorities and actors, from the first levels of education, since young children are in the process of forming the values and norms that allow achieving a harmonious coexistence in society . The objective on which this research has been directed is to determine the influence of interculturality in the teaching and learning processes of children in initial education. The methodology has been framed in the qualitative and quantitative approach, the bibliographic-documentary and field design, the exploratory research and the application of the techniques of the survey to the parents, interview with the teachers and the observation sheet to the parents. boys and girls of initial education level. The research project had as beneficiaries the students, teachers and parents of the initial education level of the Manuel Matheu Unit, allowing to clarify the knowledge around the formation of infants in the aspect of their personality to learn to respect, tolerate and share life experiences about the cultural expressions of each student. The results achieved by the research have allowed to conclude that interculturality is the contact and exchange between cultures in equitable terms, under conditions of equality, prioritizing respect and tolerance between members of different cultural groups, these qualities are learned from early childhood so it is convenient to stimulate it in initial education. There are some deficiencies in the educational process for which it has not been possible to strengthen interculturality, such as the lack of spaces for reflection and recognition of cultural diversity.